2013
DOI: 10.1177/0956797613504965
|View full text |Cite
|
Sign up to set email alerts
|

Better Off Than We Know

Abstract: Three studies examined Americans' perceptions of incomes and income inequality using a variety of criterion measures. Contrary to recent findings indicating that Americans underestimate wealth inequality, we found that Americans not only overestimated the rise of income inequality over time, but also underestimated average incomes. Thus, economic conditions in America are more favorable than people seem to realize. Furthermore, ideological differences emerged in two of these studies, such that political libera… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
38
1

Year Published

2014
2014
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 110 publications
(52 citation statements)
references
References 11 publications
(16 reference statements)
2
38
1
Order By: Relevance
“…Despite the importance of objective indicators of economic inequality and the structural barriers for social mobility, there is an equally important reason why we need to examine the consequences of inequality through a social psychological lens: growing evidence suggests that objective inequality indicators and the collectively shared perception of inequality (i.e., subjective perceptions) are not necessarily aligned. For example, studies show that people can both dramatically underestimate (Norton & Ariely, 2011) and overestimate the actual level of inequality (Chambers, Swan & Heesacker, 2014). Further, it is the subjective perceptions of inequality rather than objective inequality which predict important outcomes such as happiness (Buttrick & Oishi, 2016) and health (Adler et al, 2000).…”
Section: Objective Versus Subjective Perceptions Of Growing Inequalitymentioning
confidence: 99%
“…Despite the importance of objective indicators of economic inequality and the structural barriers for social mobility, there is an equally important reason why we need to examine the consequences of inequality through a social psychological lens: growing evidence suggests that objective inequality indicators and the collectively shared perception of inequality (i.e., subjective perceptions) are not necessarily aligned. For example, studies show that people can both dramatically underestimate (Norton & Ariely, 2011) and overestimate the actual level of inequality (Chambers, Swan & Heesacker, 2014). Further, it is the subjective perceptions of inequality rather than objective inequality which predict important outcomes such as happiness (Buttrick & Oishi, 2016) and health (Adler et al, 2000).…”
Section: Objective Versus Subjective Perceptions Of Growing Inequalitymentioning
confidence: 99%
“…To reduce the influence of response times that reflect lapses in attention, and to avoid the complete removal of genuine response times that may reflect increased difficulty in the formation of trust or aggression judgments, lengthy response times were Winsorized such that times longer than 4,000 ms were changed to 4,000 ms (greater than 2.5 SDs of the mean, 1.81% of aggression and 2.77% of trustworthiness response times). 1 The process and benefits of Winsorizing are discussed in many articles (e.g., Erceg-Hurn & Mirosevich, 2008;Ruppert, 1988;Wilcox, 2005) and Winsorizing has been used for reaction time (RT) outliers in many recent studies (e.g., Chambers, Swan, & Heesacker, 2014;Lai et al, 2012;Mueller, Makeig, Stemmler, Hennig, & Wacker, 2011;Townsend, Eliezer, Major, & Mendes, 2014;Wilkowski & Meier, 2010). A mixed factorial ANOVA with one within-subjects factor (aggression vs. trustworthiness judgments) and one betweensubjects factor (aggression rated first or second) revealed two main effects: Participants rated aggression faster than trustworthiness (F[1, 128] ϭ 29.70, p Ͻ .001, Cohen's d ϭ 0.96), irrespective of whether they rated aggression or trustworthiness first, and participants provided both judgments faster if they rated aggression first rather than second (F[1, 128] ϭ 9.03, p Ͻ .01, Cohen's d ϭ 0.53; see Figure 3b).…”
Section: Do Participants Judge Aggression Faster Than Trustworthiness?mentioning
confidence: 99%
“…Additionally, perceived economic inequality is also biased by the ideological climate, social norms, and individual beliefs. Previous research has shown that adherence to liberal political ideologies—compared to conservative ones—can lead individuals to estimate higher levels of inequality ( Chambers et al, 2014 ). What is more, there are other socio-psychological mechanisms through which people overlook and legitimate inequality, such as the acceptance of narratives related to upward social mobility ( Shariff et al, 2016 ), the endorsement of system-justifying ideologies ( Jost and Hunyady, 2005 ), and the promotion of meritocratic discourses ( Mijs, 2016 ).…”
Section: Introductionmentioning
confidence: 99%